2004
DOI: 10.1029/2004gl019455
|View full text |Cite
|
Sign up to set email alerts
|

Threshold height (h′F)c for the meridional wind to play a deterministic role in the bottom side equatorial spread F and its dependence on solar activity

Abstract: Detailed investigations have been carried out on the occurrence of bottom side Equatorial Spread F (ESF) and the thermospheric meridional wind characteristics just before the former's initiation using ground based ionospheric data corresponding to the equinoctial periods of 1993–1998, from Trivandrum (8.5°N, 76.5°E, dip = 0.5°N) and Sriharikota (13.7°N, 80.2°E, dip ∼ 10°N) in the Indian longitudes. Critical analysis of the base height of the F‐region h′F at the time of triggering of ESF and the polarity of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
51
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 51 publications
(51 citation statements)
references
References 31 publications
0
51
0
Order By: Relevance
“…They suggested that the meridional winds were the outcome of the pressure bulges associated with ETWA (Raghavarao et al, 1993). Jyoti et al (2004) brought out the dependence of the threshold height h F c , on solar activity for the equinox. In the present study, the seasonal variation in the threshold height for the triggering of ESF has been examined, corresponding to the solar minimum and maximum phases.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…They suggested that the meridional winds were the outcome of the pressure bulges associated with ETWA (Raghavarao et al, 1993). Jyoti et al (2004) brought out the dependence of the threshold height h F c , on solar activity for the equinox. In the present study, the seasonal variation in the threshold height for the triggering of ESF has been examined, corresponding to the solar minimum and maximum phases.…”
Section: Discussionmentioning
confidence: 99%
“…Only those events for which ESF is triggered before 20:00 IST are considered for this study. As mentioned earlier, the criterion of ESF occurrence irrespective of the polarity of meridional winds is applied to h F to determine the threshold height h F c below which equatorward wind is essential for the triggering of ESF (Devasia et al, 2002;Jyoti et al, 2004). Figure 1a shows the scatter plot of the meridional wind velocities against h F values of each of the ESF events during the summer solstice of solar minimum (left panel) and solar maximum (right panel) periods.…”
Section: Experimental Set Up and Data And Methods Of Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…These conditions include the movement of the F-layer to very high altitudes in the postsunset hours, and/or formation of steep bottom side F-layer electron density gradient. Aspects related to the effect of meridional winds, on ESF occurrence, have been examined by some workers (Maruyama and Matuura, 1984;Devasia et al, 2002;Jyoti et al, 2004;Manju et al, 2007). Studies on the role of seed perturbations, in the generation of F region irregularities have been reported by Whitehead (1971) and Fejer et al (1999).…”
Section: Introductionmentioning
confidence: 99%